[N]Chalcogena[N]pericyclynes: DFT studies on binaric carbon-chalcogen compounds - Werz, Daniel B.; Gleiter, Rolf (Organic letters, 2004)
DFT studies on [N]chalcogena[N]pericyclynes (n = 3−6, 8) demonstrate their relative stability and hence their possible existence as stable species. By minimizing repulsive interactions between the chalcogens' lone pairs, the molecules adopt structures that resemble, in shape, cycloalkanes or elemental chalcogens. [3]Chalcogena[3]pericyclynes may be interconverted with their valence tautomers, benzene derivatives with three fused three-membered rings.